Miss Klute is a hoot! - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
Story time goes to the dogs when Ella Mentry School gets a therapy dog to help kids with their reading skills.
Keywords: Reading -- Juvenile fiction; Labradoodle -- Juvenile fiction; Working dogs -- Juvenile fiction; Dogs -- Juvenile fiction; Schools -- Juvenile fiction; Humorous stories